Productivity enhancement of spirulina (Arthrospira platensis) using flexible floating-bed photobioreactor, mixing methods and nitrogen sources - Mohd Yazam, Mohd Shahmen (2015)
Nowadays, microalgae are becoming the focal point to solve malnutrition or malnourishment, especially in developing countries. Malnutrition significantly causes thousands of deaths especially among children. In Malaysia, mass cultivation of Spirulina has not been well explored. This is due to the lack of information and scientific data pertaining to Spirulina cultivation under Malaysian climate. Therefore, the aim of this study was to develop a new culture system for Spirulina mass cultivation. The study was conducted under outdoor condition settings. Arthrospira platensis was cultured inside flexible floating-bed photobioreactor whereas land based photobioreactor was established as control. Half concentration of standard Kosaric medium from the original amount was used in this study. Both physical and growth parameters were determined daily while the nutritional content was determined at day-8 for cycles I, II and III. The pH variations recorded normal ascending patterns throughout the cultivation period. No significant difference (p > 0.05) of dissolved oxygen concentrations was found, however, land based photobioreactor showed slightly higher reading on average. A significantly higher (p < 0.05) culture temperature recorded inside land based photobioreactor was 32.97 ± 0.50 ºC, while the culture temperature inside flexible floating-bed was 28.97 ± 1.40 ºC. No significant difference (p > 0.05) of total chlorophyll and biomass variations were observed. Both flexible floating-bed and land based photobioreactors showed no significant difference in terms of protein content (p > 0.05) but recorded higher protein content of more than 45% of 1 g cell dry weight. Both photobioreactors recorded lower lipid content of not more than 1.5% of 1 g cell dry weight. Subsequently, in outdoor environment and half strength of media concentration, A. platensis was cultured inside flexible floating-bed photobioreactor with different mixing methods namely aeration and agitation. Aeration mixing recorded significantly lower (p < 0.05) dissolved oxygen concentrations. Lower values of temperature were also recorded (p < 0.05) between flexible floating-bed photobioreactor with aeration and land based photobioreactor. Arthrospira platensis with aeration mixing contained significantly more (p < 0.05) total chlorophyll content. Biomass concentration also revealed higher values (p < 0.05) for aeration mixing compared to agitation mixing. Major differences were observed for many parameters as higher dissolved oxygen concentration inhibits cell growth significantly. On average, protein content was higher (p < 0.05) in aeration mixing up to 46.57 ± 1.53%, compared to agitation at 22.47 ± 2.17%. Vice versa, agitation mixing recorded significantly higher (p < 0.05) carbohydrate content compared to aeration mixing. No significant difference (p > 0.05) was recorded for lipid content. Specific growth rate recorded for aeration was 0.223 1/day while for agitation was 0.121 1/day. Both NaNO3 and CH4N2O displayed promising growth performance of A. platensis for outdoor cultivation inside flexible floating-bed photobioreactor. No significant difference (p > 0.05) of optical density, total chlorophyll content and biomass concentration was recorded between the two different nitrogen sources for outdoor cultivation. However, optical density and total chlorophyll recorded slightly higher readings for NaNO3 due to the nitrogen atom being readily able to be used by the cell in culture media compared to CH4N2O. Cultivation with NaNO3 as nitrogen source revealed significantly higher (p < 0.05) protein content up to 46.57 ± 1.53%. Meanwhile, CH4N2O recorded lower protein content but the synthesis of carbohydrate content was significantly higher, up to 48.08 ± 1.27%. The specific growth rate of NaNO3 was 0.223 1/day better than CH4N2O. The study indicated higher growth in flexible floating-bed with aeration. NaNO3 was better than CH4N2O. Bio-economic study has determined that the compound, CH4N2O is more cost effective as it is cheaper and readily available in the market.